KONTRAKULTUR PERWAKILAN RAKYAT: BELAJAR DARI IMPROVISASI PEMILIHAN PEMIMPIN POLITIK - Moh. Rosyid (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2013)
Leaders are persons idolized by their community or society. This is in case when they are selected through lawfull process. However, in reality, most direct election of government lead to political turbulence both in national and regional levels. Departing from this circumstance, discourse on changing the direct election to indirect system in some regions has been brought about due to social comfort. Discourse on the direct and indirect election is part of political dynamics in national and regional level. It is not taboo to be discussed, especially in academic level. This article is unfinished review of the problem with the expectation to be continued by politicians and political experts in order to understand each other and offer arguments and solutions. The dynamic discussion includes the topics of direct, indirect and collective election; the cost of the election; political dynasties; one package or separate; discrimination; and the popularity of candidates.Keywords: dynamic discourse, regional and national politics